Identification methods for Tomato brown rugose fruit virus (ToBRFV) in México - Nolasco-García, Luis Ismael; Marín-León, Juan Luis; Ruiz-Nieto, Jorge Eric; Hernández-Ruíz, Jesus (Agronomía Mesoamericana, 2020)
Introduction. The tomato brown rugose fruit virus (ToBRFV) was first reported in Israel and Jordan in 2014, causing damage to tomato crops in protected agriculture. Objective. To collect information on the known distribution, current situation, and detection methods of ToBRFV. Development. Between 2018 and 2019, the presence of the virus was confirmed in Mexico, the United States, China, Germany, Turkey, the United Kingdom, and Italy. Electron microscopy and serological tests have been used to detect the virus, but these cannot differentiate ToBRFV among other tobamoviruses. The most effective diagnostic technique for detection is specific oligonucleotides developed from the isolates from Israel and Jordan. Hygiene protocols are the most important step in preventing infections. Conclusion. Efforts to control ToBRFV are currently focused on the use of strict sanitation and detection practices in seed and plant, using molecular reverse transcriptase polymerase chain reaction (RT-PCR) techniques with specific oligonucleotides, which avoid false positives.